2009
DOI: 10.1073/pnas.0911748107
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoparticles reveal that human cervicovaginal mucus is riddled with pores larger than viruses

Abstract: The mechanisms by which mucus helps prevent viruses from infecting mucosal surfaces are not well understood. We engineered non-mucoadhesive nanoparticles of various sizes and used them as probes to determine the spacing between mucin fibers (pore sizes) in fresh undiluted human cervicovaginal mucus (CVM) obtained from volunteers with healthy vaginal microflora. We found that most pores in CVM have diameters significantly larger than human viruses (average pore size 340 ± 70 nm; range approximately 50–1800 nm).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
345
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(376 citation statements)
references
References 59 publications
29
345
2
Order By: Relevance
“…Olmsted found, using macromolecules, viruses, and polystyrene nanoparticles, an apparent pore size of 100−110 nm (agreeing with electron micrographs showing pore sizes of 20−200 nm reported in the same work), while Lai found that the diffusion rates they had recorded for poly(ethylene glycol) (PEG)-coated nanoparticles of sizes up to 500 nm required a pore size of at least 340 ± 70 nm. 8 Although the mucus used in both these works was cervicovaginal and did not contain MUC2, Macierzanka et al 6 observed that nonmucoadhesive nanoparticles as large as 2 μm were able to diffuse through porcine jejunal mucus containing MUC2 mucin at different rates depending on the local microviscosity of the mucus, including some at similar rates to water, implying an open-structured gel mesh similar to that calculated by Lai et al It is important to note that Macierzanka et al reported similar distributions of Stokes viscosities for the 500 nm nonmucoadhesive nanoparticles in both a mucin preparation similar to the one studied in this work and in an ex-vivo mucus sample that had not been purified (and thus reflects the behavior of the mucin in its native mucosal environment). The authors concluded from this that the obstruction to particle diffusivity they observed was due to the mucin and not, to a significant degree, to the presence of other mucus components.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olmsted found, using macromolecules, viruses, and polystyrene nanoparticles, an apparent pore size of 100−110 nm (agreeing with electron micrographs showing pore sizes of 20−200 nm reported in the same work), while Lai found that the diffusion rates they had recorded for poly(ethylene glycol) (PEG)-coated nanoparticles of sizes up to 500 nm required a pore size of at least 340 ± 70 nm. 8 Although the mucus used in both these works was cervicovaginal and did not contain MUC2, Macierzanka et al 6 observed that nonmucoadhesive nanoparticles as large as 2 μm were able to diffuse through porcine jejunal mucus containing MUC2 mucin at different rates depending on the local microviscosity of the mucus, including some at similar rates to water, implying an open-structured gel mesh similar to that calculated by Lai et al It is important to note that Macierzanka et al reported similar distributions of Stokes viscosities for the 500 nm nonmucoadhesive nanoparticles in both a mucin preparation similar to the one studied in this work and in an ex-vivo mucus sample that had not been purified (and thus reflects the behavior of the mucin in its native mucosal environment). The authors concluded from this that the obstruction to particle diffusivity they observed was due to the mucin and not, to a significant degree, to the presence of other mucus components.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A model is required to fit the diffusion rates and determine a mesh size for the network that will allow passage of the particles. Olmsted et al 4 and Lai et al 8 used a model describing homogeneous hydrogels, 45,46 a model appropriate for a physically entangled linear polymer system. Olmsted found, using macromolecules, viruses, and polystyrene nanoparticles, an apparent pore size of 100−110 nm (agreeing with electron micrographs showing pore sizes of 20−200 nm reported in the same work), while Lai found that the diffusion rates they had recorded for poly(ethylene glycol) (PEG)-coated nanoparticles of sizes up to 500 nm required a pore size of at least 340 ± 70 nm.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Although, few studies have conclusively addressed the role of size in dictating mucosal immunity following oral delivery, there is a consensus that particles with a diameter smaller than 1 μm are more readily taken up by M cells [190]. In addition to the role of size in regulating the potential for trans-epithelial uptake, the ability of particles to migrate through the pores in the mucus is dependent on both size and surface electrochemical properties [33,191]. While M cells remain a key target for particulate oral vaccines, it was recently shown that particles of 1-5 μm in size were taken up across the jejunum and ileum via non phagocytic processes, suggesting that particle uptake is not solely via M cells [192].…”
Section: Synthetic Particle-based Strategiesmentioning
confidence: 99%
“…Particles with sizes below 10 µm are well taken up in the GI tract but uptake occurs more favourably when sizes are below 1000 nm (Jani et al, 1989;Kreuter, 1991;Shakweh et al, 2005). In addition, the mesh-pore spacing of the intestinal 295 mucosal barrier is 50-1800 nm (Lai et al, 2010;Primard et al, 2010).…”
mentioning
confidence: 90%